1997
DOI: 10.1136/oem.54.10.756
|View full text |Cite
|
Sign up to set email alerts
|

Outcome determinants for isocyanate induced occupational asthma among compensation claimants.

Abstract: Objectives-To compare the outcome of occupational asthma (OA) induced by isocyanates in Ontario (where a surveillance programme for exposed workers has been in place for over 15 years), with the outcome of OA induced by other work agents.Methods-Compensated OA claims during the period 1984-88 in Ontario were retrospectively reviewed in a standardised way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
63
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 14 publications
(1 reference statement)
5
63
0
Order By: Relevance
“…In this program a number of core variables are collected from cases meeting defined criteria for WRA. The pattern of agents implicated in these reports is of interest (Table 1) The diisocyanate group of chemicals, which are used in the production of a wide variety of consumer and commercial products, represented the largest single group of agents-a finding similar to that reported from several other countries (18,19,23). Contamination in nonindustrial workplaces such as offices and schools represented the second largest group of agents reported in association with asthma onset.…”
Section: Work-related Asthma Surveillancementioning
confidence: 59%
See 1 more Smart Citation
“…In this program a number of core variables are collected from cases meeting defined criteria for WRA. The pattern of agents implicated in these reports is of interest (Table 1) The diisocyanate group of chemicals, which are used in the production of a wide variety of consumer and commercial products, represented the largest single group of agents-a finding similar to that reported from several other countries (18,19,23). Contamination in nonindustrial workplaces such as offices and schools represented the second largest group of agents reported in association with asthma onset.…”
Section: Work-related Asthma Surveillancementioning
confidence: 59%
“…Thus, occupational intervention studies have indicated that control of antigen exposure can both reduce symptoms and specific IgE among sensitized individuals as well as prevent the onset of sensitization among newly exposed individuals. Clinical follow-up among persons with occupational asthma caused by a variety of agents has indicated that prompt control of exposures is associated with a better chance of improvement or resolution of symptoms and findings, whereas workers who have continued exposures have a poorer prognosis (23,48).…”
Section: Work-related Asthma: Preventive Interventionsmentioning
confidence: 99%
“…In terms of long-term outcome, despite complete avoidance of exposure, PARK and NAHM [3] showed a spectrum of responses in subjects with isocyanate asthma and proposed that the final outcome depends on which mechanism is predominant in each individual. The majority of the follow-up studies on isocyanate asthma [4][5][6][7][8][9][10][11] emphasised that only one-half of subjects with isocyanate asthma will recover, while one-half of those who do not recover will show some improvement, and one-half will complain of asthmatic symptoms and will require anti-asthma therapy. Short duration of exposure to isocyanates and of symptoms before the diagnosis, immediate cessation of exposure after diagnosis, young age, milder degree of nonspecific airway hyperresponsiveness and presence of specific immunoglobulin (Ig)E antibodies to isocyanates have been found to be associated with a favourable prognosis.…”
mentioning
confidence: 99%
“…3 There is clear evidence that the prognosis for workers developing occupational asthma is improved by rapid accurate diagnosis and removal from further allergen exposure. [9][10][11][12] Studies from a range of countries, however, have identified average delays of several years in the patient journey for symptomatic workers, which in part relate to the condition being under-recognised in primary care. [13][14][15][16] National published guidelines for the prevention, The full version of this paper, with online Appendix, is available at www.thepcrj.org …”
Section: Introductionmentioning
confidence: 99%
“…This is highly relevant for affected workers, since early and accurate diagnosis linked with exposure modification offers the best prognosis, both for health and socioeconomic outcomes. [4][5][6][7][8][9][10][11][12] It is clear therefore that adequate primary care training is vital to ensure that adult asthmatics with workrelated symptoms are identified as soon as possible in order to facilitate specialist diagnosis and management. 17,19 The problem of ensuring that occupational asthma guidelines are utilised in primary care is not unique to the UK, and has recently also been acknowledged by American and Canadian occupational respiratory disease specialists.…”
mentioning
confidence: 99%